Improving manganese circular economy from cellulose by chelation with siderophores immobilized to magnetic microbeads - Peter M. Kunz; Kerstin Mörtter; Ralf Müller; Isabell Sommer; Philipp Weller; Jeff Wilkesman (Environment, Development and Sustainability, 2020)
Manganese (Mn) contained in cellulose is partially responsible for an increased consumption of paper bleaching chemicals (like O2, H2O2), consequently diminishing the efficiency in pulp processing, darkening the pulp and deteriorating pulp quality. Usually, Mn in the paper industry is removed employing the environmentally critical EDTA. A greener alternative constitutes, however, the use of siderophores, high-affinity metal-chelating organic compounds that are produced by microorganisms to acquire metals (Fe and Mn among others), like desferrioxamine B (DFOB) or desferrioxamine E (DFOE). The use of native Mn-transporter proteins, like PratA, constitutes another possibility for Mn removal. The evaluation of utilizing siderophores or PratA for Mn removal from cellulose in a circular economy scheme is therefore essential. Firstly, Mn removal from cellulose was performed by immobilizing siderophores or PratA on magnetic beads (M-PVA~C22). Secondly, the beads were incubated overnight with a 2% cellulose suspension, allowing Mn-ligand complex formation. Finally, cellulose suspensions were submitted for Mn quantification, employing either the TCPP [Tetrakis(4-carboxyphenyl)porphyrin] method, the PAN [1-(2-pyridylazo)-2-naphthol] method or the Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). When non-immobilized ligands were employed, a 31% Mn removal was achieved; when using immobilized ligands, around 10% Mn removal was obtained. Treated and untreated cellulose was analyzed by SEM and the Mn distribution between the solid and liquid phase was parameterized using adsorption isotherm models. This novel greener method proved to be feasible and easy, leading to potential improvements in the paper industry. Next research steps are to optimize Mn removal and quantify Mn recovery after ligand decoupling before scaling-up.
Keywords: 330; Circular economy; ICP-OES; Manganese; Siderophores